A micro-anatomical comparison of goat jaw cancellous bone with human mandible: Histomorphometric study for implant dentistry - Tamal Kanti Pal; Abhijit Chakraborty; Sohini Banerjee (Wolters Kluwer Medknow Publications, 2014)
Aim/Background: To compare human jaw micro-anatomy with goat jaw to find a suitable animal model for various biomechanical experiments with dental implants. Materials and Methods: Fifteen fresh goat jawbones (mandibles) were collected from slaughterhouse and five dried human skull bones (mandibles) were collected from the anatomy department of various medical colleges in Kolkata. All the jawbones were then vertically sectioned, processed, stained, and suitably viewed under an optical microscope to evaluate the minimum trabecular width in coronal, middle, and apical areas of the alveolar bone. A total of 150 such samples were evaluated for goat and human mandible. Results and Observations: The trabecular width of goat alveolar bone was found to be greatest in coronal area (62.99 μm) and the least in apical area (41.13 μm). The width of human mandibular trabeculae was greatest in coronal area (67.65 μm), and the least in apical area (40.17 μm). Conclusion: There is a similarity of micro-anatomical dimensions between goat and human mandibles, and hence, suitable for many implant experiments concerning biomechanical testing.